Scattering from (p, q)-strings in AdS5 × S5 - Silviu S. Pufu; Victor A. Rodriguez; Yifan Wang (Journal of High Energy Physics)
Abstract Motivated by understanding the scattering of gravitons and their superpartners from extended (p, q)-strings in type IIB string theory via AdS/CFT, we study an integrated two-point function of stress tensor multiplet operators in the presence of a half-BPS line defect in N $$ \mathcal{N} $$ = 4 SU(N) super-Yang-Mills theory. We determine this integrated correlator at the five lowest non-trivial orders in 1 / N $$ 1/\sqrt{N} $$ at fixed Yang-Mills coupling and θ angle. Our calculations are performed explicitly when the line defect is a Wilson line, in which case we find a finite number of perturbative contributions at each order in 1 / N $$ 1/\sqrt{N} $$ , as well as instanton contributions. Using SL(2, ℤ) transformations, our results can also be applied to Wilson-’t Hooft line defects dual to extended (p, q)-strings in the bulk. We analyze features of these integrated correlators in the weak coupling expansion by comparing with open-closed amplitudes of type IIB string theory on AdS5 × S5, as well as in its flat space limit. We predict new higher-derivative interaction vertices on the D1-brane and, more generally, on (p, q)-strings.